Examining the Impact of Different Street Classification Scenarios on Active Transportation Equity. Insights from Athens, Greece - Stefanos Tsigdinos (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
Transport equity is an essential characteristic of a just city and a concept related to social inclusion. This study examined how different street classification scenarios will affect active transportation equity. Four different scenarios with different planning rationales were developed that reformulate the street classification in a municipality within a metropolitan area, i.e., Kallithea in Athens, Greece. These scenarios give rise to new street categories that reallocate street space favoring active transport users. The evaluation of active transportation equity was carried out by utilizing spatial analysis and welfare economics through the lens of egalitarian and sufficientarian approaches. Based on the results, scenarios that propose new urban centers as well as a readable street classification with traffic calming zones determined by ring roads seem to be more efficient in accommodating vulnerable users in an equitable way. Hence, new planning schemes should rely on active modes, leaving automobiles behind. In general, measuring the impact of street classification scenarios through the lens of equity is critical for improving the quality of life in cities. Additionally, it is noteworthy knowledge for policy makers, planners, and local administrators. Finally, this research may inspire new studies, enriching the scientific debate.